2004
DOI: 10.1051/cocv:2004013
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of error bounds for lower semicontinuous functions on metric spaces

Abstract: Abstract.Refining the variational method introduced in Azé et al. [Nonlinear Anal. 49 (2002) 643-670], we give characterizations of the existence of so-called global and local error bounds, for lower semicontinuous functions defined on complete metric spaces. We thus provide a systematic and synthetic approach to the subject, emphasizing the special case of convex functions defined on arbitrary Banach spaces (refining the abstract part of Azé and Corvellec [SIAM J. Optim. 12 (2002) 913-927], and the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 25 publications
1
103
0
Order By: Relevance
“…(Strong slope) Let us recall from [22] (see also [32], [6]) the notion of a strong slope defined for every x ∈ dom f as follows:…”
Section: Notation (Multivalued Mappings)mentioning
confidence: 99%
See 2 more Smart Citations
“…(Strong slope) Let us recall from [22] (see also [32], [6]) the notion of a strong slope defined for every x ∈ dom f as follows:…”
Section: Notation (Multivalued Mappings)mentioning
confidence: 99%
“…This fact is strongly connected to famous classical results in this area (see [23,45,32,49] for example) and in particular to the notion of ρ-metric regularity introduced in [32] by Ioffe. Using results on global error-bounds of Ioffe [32,33,34] (see also Azé-Corvellec [6]) we show that some global forms of the K L-inequality, as well as metric regularity, are both equivalent to the "Lipschitz continuity" of the sublevel mapping…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recall from [39], (see also [40] and the discussion in [38]) that the local slope and the nonlocal slope (see, e.g., [41]) of the function f at x ∈ dom f , are the quantities denoted respectively by |∇ f |(x) and |Γ f |(x). Using the notation…”
Section: Slope Characterizations Of Directional Hölder Metric Regularitymentioning
confidence: 99%
“…Our main objective in this paper is to use the theory of error bounds to study the metric regularity of implicit multifunctions. The approach based on error bounds to investigate the metric regularity has been recently used in [6] and in [46] to study implicit multifunctions in smooth spaces. Especially in the survey paper [5], it was shown that this approach is powerful to provide a unified theory of the metric regularity.…”
Section: Introductionmentioning
confidence: 99%